The Yin and Yang of Artificial Intelligence - Javed, Kainat (Journal of University College of Medicine and Dentistry, 2024)
Artificial Intelligence holds the ability to transform medical education by improving the efficiency of training programs, enabling personalized learning, and providing new tools for evaluation and assessment. However, with any new technology, there are also potential risks and concerns that must be acknowledged. The use of AI in medical education raises concerns about privacy, ethical dilemmas, and the possibility of biased algorithms. It is vital to be aware of these potential threats and work to reduce them to ensure that AI is used in an ethical and responsible manner. By doing so, the potential benefits of AI in medical education can be enhanced while minimizing its drawbacks.